Personalization in VR and Designing Personalized VR Office Design Tool Exploring the personalization in VR offices and a preliminary research for designing tool - for creating personalized VR offices. - AKYOL, DAMLA (My University, 2018)
Virtual reality environments are recently developing at a fast rate and gaining much attention from many people around the world. One of the possible usages of virtual and augmented reality is with our offices. The offices people use are usually very restrictive and not many people get to say anything about the kind of office they might have. With virtual reality, it is possible to create a whole new environment suitable for the person and improve productivity a lot. One big aspect of virtual reality offices is the personalization. As every person has different characteristics and habits, making the office suit to a person is very essential since they will spend the majority of their daily life in there. However a big problem with creating personalized VR offices is that it requires too much time. In order to decrease the time spent on making these offices, an application that uses standardized assets in order to combine them and create a personalized VR office is decided to be researched and designed. In order to find which aspects of the VR offices make people feel most in control and feel like the offices are made for them, testings of some basic prototypes of offices are done. After researching and interviewing, three people are chosen to further investigate their habits and office usage, and their desired VR offices are created. With these offices, multiple usability tests are done and importance of location, sounds, and the manipulation of the objects in the offices are found to be the most important aspects. With this information, sketches and prototypes are made for the office creation tool.